La escritura de la lengua judeo-española - Czöndör, Klára (Verbum – Analecta Neolatina, 2008)
This paper discusses the writing system of the Sephardic Jews, who were expelled from the Iberian peninsula in 1492. After a short description of the history of the Spanish Jews, the Jewish languages are described in general, then the Judeo-Spanish language in particular. In connection with the writing systemof the language under discussion, a detailed description is provided of the varieties that use Hebrew characters when writing in Spanish, followed by an account of the systems that came into existence following the introduction of the writing system based on Latin letters. Related to the orthography of the Judeo-Spanish language, the pros and cons of the writing system using diacritics and the "Aki Yerushalayim system" are discussed. Issues such as the maintenance of the language and its standardization are also touched upon.